The value of ultra sonogram in the diagnosis of ovarian dermoid cysts - Pradhan, Sujan (Journal of Kathmandu Medical College, 2014)
Mature cystic teratoma often referred to as dermoid cysts have been diagnosed using all imaging modalities. Dermoid cysts present various and complex ultrasonographic aspects. At times diagnosis may be difficult and lead to confusion due to its complex solid and cystic nature. The specificity for diagnosis of fat and calcification makes computed tomography (CT) scan the modality of choice. But CT scan is high technique equipment, expensive and may not be affordable or available at all places. Advances in the quality of USG machines, better experiences of ultrasound operators and thorough analysis of all ultrasound features that characterise dermoid cysts have resulted in an increased accuracy of exact ultrasonographic diagnosis of dermoid cysts in the vast majority of the cases and now used as the first preoperative work-up method of choice for the assessment of adnexal masses in clinical practices. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10920 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 26-31